Determination Of Technology-Based Accounting Curriculum Through Financial Literacy - Khairin, Fibriyani Nur; Syakura, Muhammad Abadan; *, Irwansyah (Accounting Department,, 2022)
Purpose This study aims to determine which factors can affect financial literacy as the basis for developing a technology-based accounting curriculum at the Accounting Department, Faculty of Economics and Business, Mulawarman University. Design/methodology/approach This research is a quantitative study using primary data obtained through a questionnaire filled out by 100 respondents. The data is then processed using Smart-PLS. Findings The results showed that financial behavior and financial attitudes had a positive effect on financial literacy, while financial technology did not affect financial literacy. This proves that the behavior and attitudes shown by the Faculty of Economics and Business students can increase student curiosity regarding financial management and understanding of financial instruments to improve student financial literacy. In addition, from the respondents' answers, it can also be seen that the literacy level of students is at a sufficient literate level, which means that students have a good understanding of financial management but are still unable to maximize the use of financial products and services. The lack of students' use of financial technology is evidence of this. Practical implications The results of this research contribute to the Accounting Department needing to add material about the benefits and functions of financial technology in financial management to improve student competence in the industrial era 4.0. Originality/value This paper presents financial literacy as the basis for improving a technology-based curriculum that is currently indispensable in accounting education. Keywords : Financial Literacy; Financial Technology; Financial Attitude; Accounting Curriculum Paper-type Case study